Proceedings of the 14th ACM / IEEE International Symposium on Empirical Software Engineering and Measurement (ESEM) 2020
DOI: 10.1145/3382494.3410672
|View full text |Cite
|
Sign up to set email alerts
|

What Industry Wants from Requirements Engineers in China?

Abstract: Background] Publications on the professional occupation of Requirements Engineering (RE) reported on market demands for both RE and non-RE qualifications and indicated the state-of-the-practice of RE roles in industry. However, prior research was not from the perspective of the RE area in the Software Engineering Body of Knowledge (SWEBOK). Nor, they shed light on the industry needs of RE professionals in China. [Aims] This paper focused on RE-specific tasks and skills sought after in China, from the perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…On the one hand, keyword searches to find related job posts were mentioned in two studies. The keywords found in the literature were used to conduct the automatic search in the T-Net portal [64], while the other research used four keywords derived from work experiences based on the authors and descriptions of the role [65]. On the other hand, the data were collected using predefined search criteria to collect software-related advertisements [49].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, keyword searches to find related job posts were mentioned in two studies. The keywords found in the literature were used to conduct the automatic search in the T-Net portal [64], while the other research used four keywords derived from work experiences based on the authors and descriptions of the role [65]. On the other hand, the data were collected using predefined search criteria to collect software-related advertisements [49].…”
Section: Data Collectionmentioning
confidence: 99%
“…The sample size was calculated using an online tool by adding the LinkedIn estimated interested population size as 3689, where the confidence level and margin of error were set as 95% and 3%, respectively. In the literature, two studies were found to use the same method to calculate the sample size [49,65]. The sample size was generated as 828 but there were 900 sample data collected, as per Table 3.…”
Section: Datasetmentioning
confidence: 99%
“…The market appetite of Requirement Engineers (RE) is explored across three countries Netherlands, Canada and China, in the year 2015, 2017 and 2019 respectively, where job ads analysis is applied [12][13][14]. All three studies adopt a similar empirical research method that collects a wide range of RE position ads, selects a relevant data set, and then apply coding, analysis and synthesis to the qualitative data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The 2017 Canadian study adopted a two-round selection workflow of the collected job ads, where the first round of selection is by job title and overview, the second round by job responsibility, and lastly removing duplications [13]. The 2019 Chinese study highlights a pilot data selection on a 160 job ads sample, where author 1 and author 2 both select the relevant jobs from the 160 job ads respectively and compare the results, based on a 90%+ consensus and the selection criteria is verbally agreed between the authors, which has increased the credibility of the data selection [14]. [12][13][14] analyzed tasks and skills in groups according to the data, and rankings of skills are drawn out from the job ads, interpreted and compared in detail.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation